PROBLEMS AND PERSPECTIVES OF IMMUNOPROPHYLAXIS IN RUSSIA - V.К. Tatochenko (Вопросы современной педиатрии, 2009)
This article presents new calendar of immunoprophylaxis in Russia, functioning since 2008, with author’s comments to its innovations. Mass vaccination against influenza was added to other ones, presenting in calendar earlier. The age limits of vaccination against hepatitis B, rubella, and measles were enlarged, and scheme of vaccination against hepatitis B was changed. This article describes new opportunities of immunoprophylaxis, that didn’t find its place in calendar yet.Key words: children, immunoprophylaxis, vaccination calendar.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(1):114-120)